Polynomial methods in optimal control and filtering - Hunt, K. J. 1963- (Kenneth J.). (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1993)
This book aims to demonstrate the power and breadth of polynomial methods in the control of engineering systems and the filtering of signals. Using commissioned contributions from renowned international specialists, the book progresses logically from the necessary background material (given at a tutorial level), through recent theoretical and practical developments, to detailed presentation of numerical algorithms.
Electronic reproduction.
Keywords: Automatic control -- Mathematics; Polynomials; Filters (Mathematics); Electronic books